(untitled) (Majalah Kedokteran Bandung, 2025)
Peppermint has several benefits, such as antibacterial, anti-inflammatory, and antifungal properties, that leads to its use in various products, especially in herbal medicine. This study aimed to evaluate the LD50 value of peppermint suspension through an acute toxicity test. This study was conducted at the Animal Laboratory Management Unit of the School of Veterinary Medicine and Biomedical Sciences, IPB University, from October 9 to 30, 2024. A total of 25 female mice were divided into 5 groups, and given different doses of peppermint suspension of 0, 0.5, 1, 1.5, and 2.0 g/kgBW. Observations were then carried out for 14 days on the parameters of body weight, physiological responses, clinical symptoms, absolute and relative organ weight, body weight, and number of mortalities per day. Results showed that the highest mortality was found in the groups administered with a 1.5 and 2.0 g/kgBW of peppermint suspension. Clinical symptoms, such as hair standing, lethargies, and decreased locomotor activity were also observed in these groups. In addition, the administration of peppermint suspension in mice had no significant effect on body weight, as well as on absolute and relative organ weight, It was also demonstrated that organs collected did not present any significant lesion. Thus, the acute toxicity test of peppermint suspension showed no macroscopic lesion or changes in organs and body weight. The LD50 value suggested that the is in the moderate toxicity category, with an LD50 value of 1.92 g/kgBW.